Stalled DNA Replication Forks at the Endogenous GAA Repeats Drive Repeat Expansion in Friedreich’s Ataxia Cells - Jeannine Gerhardt (Cell Reports, 2016)
Friedreich’s ataxia (FRDA) is caused by the expansion of GAA repeats located in the Frataxin (FXN) gene. The GAA repeats continue to expand in FRDA patients, aggravating symptoms and contributing to disease progression. The mechanism leading to repeat expansion and decreased FXN transcription remains unclear. Using single-molecule analysis of replicated DNA, we detected that expanded GAA repeats present a substantial obstacle for the replication machinery at the FXN locus in FRDA cells. Furthermore, aberrant origin activation and lack of a proper stress response to rescue the stalled forks in FRDA cells cause an increase in 3′-5′ progressing forks, which could enhance repeat expansion and hinder FXN transcription by head-on collision with RNA polymerases. Treatment of FRDA cells with GAA-specific polyamides rescues DNA replication fork stalling and alleviates expansion of the GAA repeats, implicating DNA triplexes as a replication impediment and suggesting that fork stalling might be a therapeutic target for FRDA.